The Effect of Feeding Time Food Growth Performance and Survival Rate of Red Tilapia (Oreochromis niloticus) using Recirculation System - Rajagukguk, Elisabet; Mulyadi, Mulyadi; Usman MT, Usman MT (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research aim to determine the effect of feeding time on the growth performance and survival  rate of red tilapia (Oreochromis niloticus) by using Recirculation System. This research was conducted on March-May 2018 at Technical Service Unit (UPT) of Bengkalis, Province Riau. This research was using experimental method by completely random design (RAL) one factor with three replications. The treatments were: 1. Feeding twice a day, 2. feeding three times a day, 3. Feeding four times a day and 4. Feeding five times a day. The feed given is pellet PF-800 with the amount of 4% of fish a day weights everyday. The results showed that a different feeding times influenced the growth performance and survival rate of red tilapia using recirculation system. In addition, it  also  affected  the  absolute  weight  growth,  absolute  length  growth,  feed efficiency and feed conversion ratio. The best feeding time was three times daily because it showed significantly different results compared to feeding times twice, four times, and five times a day. So that while being applied in terms of economy, feeding three times a day was the most efficient by giving the absolute weight growth was 13,23 g, specific growth rate was 2,86% survival rate was 86,67% feed efficiency was 184,80 %  and feed conversion ratio was 0,53%. Keywords: recirculation system, red tilapia, feeding time food